Patterns and Characteristics of Amphetamine-type Stimulant Use in a North-eastern State of India: A Cross-sectional Study - Ravindra Rao; Ragul Ganesh; Kunal Kishore; Ira Madan; Bhagwati Khandpal; Charanjit Sharma (Indian Journal of Psychological Medicine)
Background: South Asia generally reports low levels of amphetamine-type stimulant (ATS) use, with few studies on the pattern of ATS use. We assessed the pattern of ATS use and associated high-risk behavior in Manipur, a north-eastern state of India. Methods: 209 adult male ATS users (mean age 28.8 years) from three districts of Manipur were interviewed. Data were collected on the patterns of high-risk behavior with ATS use, health consequences, and help-seeking. The severity of use with various substances was assessed using the Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST). Depression and anxiety were assessed by the Patient Health Questionnaire (PHQ-9) and Generalized Anxiety Disorder (GAD-7) scale, respectively. Results: The mean duration of ATS use was 3.7 years (SD 2.3). The majority used ATS almost daily (88%) and depended on ATS (77%). Methamphetamine (99.5%) was the most used ATS orally. Around 87% also suffered from opioid dependence. About 76% injected drugs, most commonly heroin. Almost three-fourths (78%) used ATS before their sexual intercourse, 31% of whom did not use condoms. Most reported physical problems with ATS and had above-cut-off scores on PHQ-9 and GAD-7. The majority (95%) reported that they could procure ATS easily. Also, the majority (93%) had thought of quitting ATS use. Conclusions: Most ATS users start using ATS at a young age and have comorbid other drug use, including heroin. ATS use is associated with various physical and psychological problems. Focusing on ATS use in India and developing strategies to address this problem is essential.